[Mrs. Mihály Polcsán 8]
Lupa-island in the garden, grandparents & children, playing in the garden around the house, company eat & drink, view from the flat to the street, Christmas, little bell, litlte watching the camera, family photos, newspaper-reading in the balkon, in the kitchen, dinner eatin&drinking, 1976 Stockholm, little child&parents